A model to estimate vertical speed of ascending evacuation from maximal work capacity data. (November 2016) - Kuklane, Kalev; Halder, Amitava
Highlights: A thorough overview of all used sources for model development are given. An ascending evacuation model was developed based on maximal physical capacity. Limitations are listed with suggestions for further research to solve the problems. Abstract: This paper describes the development of an ascending evacuation model based on physical work capacity of a selected sample. The model is based on the combination of several field experiments, existing databases and pre-tests that were combined to define initial test conditions in the laboratory environment on a step machine. Maximal oxygen consumption (VO2 max) of 13 male and 12 female subjects (data was pooled), was measured, and they climbed at 3 step rates specified according to individual percentage of their maximal aerobic capacity (%VO2 max) levels. The first nineteen subjects were used for model development and the last six for validation. The paper gives an overview on the collected laboratory data and puts it into relation with the field data from both oxygen consumption and heart rate perspective. The maximum vertical displacement ( h vert in m/min) can be calculated according to: hvert  = −21.7727 + 0.4024 ∗ VO2 max + 0.2658 ∗ %VO2 max. The discussion covers limitations and possibilities of the model and suggests the literature and databases that form the basis for practical use of the prediction model. Paper defines the needs for future work and possible information sources to improve the model.